2017
DOI: 10.1152/ajpgi.00045.2017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nitric oxide-mediated inhibition of purine neurotransmitter release in the colon in the absence of interstitial cells of Cajal

Abstract: Regulation of colonic motility depends on the integrity of enteric inhibitory neurotransmission mediated by nitric oxide (NO), purine neurotransmitters, and neuropeptides. Intramuscular interstitial cells of Cajal (ICC-IM) and platelet-derived growth factor receptor-α-positive (PDGFRα) cells are involved in generating responses to NO and purine neurotransmitters, respectively. Previous studies have suggested a decreased nitrergic and increased purinergic neurotransmission in ( ) mice that display lesions in IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…ICC-IM are important because they form close, synaptic-like contacts with the terminals of enteric motor neurons, make gap junctions with SMCs, and express receptors, second messenger pathways and effector mechanisms necessary for enteric motor neurotransmission (Daniel & Posey-Daniel, 1984;Burns et al 1996;Wang et al 2000;Ward et al 2000;Beckett et al 2002Beckett et al , 2005Cobine et al 2010Cobine et al , 2011Cobine et al , 2014Blair et al 2012;Groneberg et al 2013;Sung et al 2018). Animals lacking ICC-IM or with genetic deletion of ICC-specific signalling molecules important for neurotransduction display abnormal post-junctional neuronal responses in GI organs (Burns et al 1996;Ward et al 1998Beckett et al 2002Beckett et al , 2017Duffy et al 2012;Lies et al 2014Lies et al , 2015Durnin et al 2017;Sung et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ICC-IM are important because they form close, synaptic-like contacts with the terminals of enteric motor neurons, make gap junctions with SMCs, and express receptors, second messenger pathways and effector mechanisms necessary for enteric motor neurotransmission (Daniel & Posey-Daniel, 1984;Burns et al 1996;Wang et al 2000;Ward et al 2000;Beckett et al 2002Beckett et al , 2005Cobine et al 2010Cobine et al , 2011Cobine et al , 2014Blair et al 2012;Groneberg et al 2013;Sung et al 2018). Animals lacking ICC-IM or with genetic deletion of ICC-specific signalling molecules important for neurotransduction display abnormal post-junctional neuronal responses in GI organs (Burns et al 1996;Ward et al 1998Beckett et al 2002Beckett et al , 2017Duffy et al 2012;Lies et al 2014Lies et al , 2015Durnin et al 2017;Sung et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3 Colonic migrating motor complexes (CMMC) is known as the main form of colonic transit, and it has been demonstrated that its generation is regulated by the SIP syncytium comprising of smooth muscle cells (SMCs), interstitial cells of Cajal (ICC), and platelet-derived growth factor receptor α-positive (PDGFRα + ) cells that are electrically coupled from smooth muscle tissue. [4][5][6] Thus, the tone of the colonic smooth muscle is a pivotal factor for generating motor activity and permitting changes in volume to accommodate stool in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, recent studies have shown that only a small amount of the neurotransmitter released by the varicose body of nerve terminal directly spreads to the smooth muscle to play a regulatory role, but the majority of neurotransmitters for the regulation of smooth muscle are not directly conducted by neurotransmitters, such as nitric oxide (NO), released from the enteric nervous system, but through the SIP syncytium consisting of SMC, intramuscular ICC (ICC-IM), and PDGFRα + cells. 6,9 ICC have been accepted by most researchers to integrate neuronal signals to the SMC syncytium in order to guarantee functional GI motility. 14 The function of NO in mediating effects for ICC indicate that basal enteric NO release probably acts via myenteric ICC to influence the generation of spontaneous contractions.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the enhanced purinergic signaling exists in the STZ‐induced diabetic mice. It has been reported that the purinergic neurotransmission may compensate for the decreased nitrergic neurotransmission when NOS‐positive neurons or ICC are decreased . This may underlie the up‐regulation of purinergic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%